OER Quality and Adaptation in K-12: Comparing Teacher Evaluations of Copyright-Restricted, Open, and Open/Adapted Textbooks - Kimmons, Royce (International Review of Research in Open and Distributed Learning, 2015)
Conducted in conjunction with an institute on open textbook adaptation, this study compares textbook evaluations from practicing K-12 classroom teachers (n = 30) on three different types of textbooks utilized in their contexts: copyright-restricted, open, and open/adapted. Copyright-restricted textbooks consisted of those textbooks already in use by the teachers in their classrooms prior to the institute, open textbooks included alternatives from CK-12 and OpenStax, and open/adapted consisted of open textbooks that the teachers devoted time to adapting to their individual needs. Results indicate that open/adapted textbooks were evaluated as having the highest quality, and that open textbooks were of higher quality than copyright-restricted textbooks. Though some factors of quality might be influenced by cost differences (e.g., timeliness and the ability to adopt updated textbooks), results reveal that open and open/adapted textbooks may do a better job of meeting the needs of K-12 teachers in a variety of ways that may not be captured through traditional approaches to quality assurance. This study marks an early step in exploring the quality of K-12 open educational resources (OER) and the use of practicing teachers as authentic evaluators of textbooks for their local contexts.